Peran Pembelajaran Matematika Integrasi Keislaman dalam Membangun Karakter Siswa - Supiarmo, M. Gunawan; Faqihi, Ahmad; Habiburrahman, Muhammad; Hidayah, Agus Sofian Eka (LP2M, Institut Agama Islam Qamarul Huda, 2025)
Mathematics learning integrated with Islamic values is a strategic approach to shaping the character of students who are not only intellectually intelligent but also have noble character. This study aims to examine the impact of the integration of Islamic values in mathematics learning on student character formation. The method used is a literature study with a qualitative approach through the analysis of various relevant academic sources. The study results indicate that values such as honesty, responsibility, and piety can be effectively instilled through the integration of mathematics material with an Islamic context. This approach has been proven to support students' cognitive and spiritual development and is relevant to national education goals.